NK Cells Are Not Required for Spontaneous Autoimmune Diabetes in NOD Mice - Beilke, Joshua N. (Public Library of Science, 2012)
NK cells have been shown to either promote or protect from autoimmune diseases. Several studies have examined the role of receptors preferentially expressed by NK cells in the spontaneous disease of NOD mice or the direct role of NK cells in acute induced disease models of diabetes. Yet, the role of NK cells in spontaneous diabetes has not been directly addressed. Here, we used the NOD.NK1.1 congenic mouse model to examine the role of NK cells in spontaneous diabetes. Significant numbers of NK cells were only seen in the pancreas of mice with disease. Pancreatic NK cells displayed an activated surface phenotype and proliferated more than NK cells from other tissues in the diseased mice. Nonetheless, depletion of NK cells had no effect on dendritic cell maturation or T cell proliferation. In spontaneous disease, the deletion of NK cells had no significant impact on disease onset. NK cells were also not required to promote disease induced by adoptively transferred pathogenic CD4(+) T cells. Thus, NK cells are not required for spontaneous autoimmune diabetes in NOD mice.